2012
DOI: 10.6064/2012/829504
|View full text |Cite
|
Sign up to set email alerts
|

Contribution ofα- andβ-Adrenergic Mechanisms to the Development of Pulmonary Edema

Abstract: Endogenous or exogenous catecholamines can induce pulmonary edema (PE). This may occur in human pathologic conditions such as in pheochromocytoma or in neurogenic pulmonary edema (NPE) but can also be provoked after experimental administration of adrenergic agonists. PE can result from stimulation with different types of adrenergic stimulation. With α-adrenergic treatment, it develops more rapidly, is more severe with abundant protein-rich fluid in the alveolar space, and is accompanied by strong generalized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 103 publications
(142 reference statements)
0
22
0
1
Order By: Relevance
“…It is also possible that it could be due to excessive sympathetic drive . There are studies which report that while administration of large doses of alpha-adrenergic agonists such as phenylepinephrine result in pulmonary edema (Rassler, 2012), administration of alpha-receptor antagonists such as phentolamine reduce it markedly (Davison et al, 2012;Rassler, 2012). In a study which compared the effects of various vasodilators on the hemodynamic parameters of HAPE, it was observed that phentolamine alone and in combination with oxygen provided the maximum benefit emphasizing the significance of the sympathetic nervous system in HAPE.…”
Section: Rat As An Animal Model Of Hapementioning
confidence: 99%
“…It is also possible that it could be due to excessive sympathetic drive . There are studies which report that while administration of large doses of alpha-adrenergic agonists such as phenylepinephrine result in pulmonary edema (Rassler, 2012), administration of alpha-receptor antagonists such as phentolamine reduce it markedly (Davison et al, 2012;Rassler, 2012). In a study which compared the effects of various vasodilators on the hemodynamic parameters of HAPE, it was observed that phentolamine alone and in combination with oxygen provided the maximum benefit emphasizing the significance of the sympathetic nervous system in HAPE.…”
Section: Rat As An Animal Model Of Hapementioning
confidence: 99%
“…Before surgery, the patient developed non-cardiogenic pulmonary edema, which is rarely seen in those with pheochromocytoma [6]. Given that there was an abnormal increase in IL-6 levels, the pulmonary edema could have been attributed to the inflammatory mechanism, by which the overproduction of IL-6 caused from elevated catecholamine levels disrupts the endothelial junction, leading to capillary leakage [6].…”
Section: Discussionmentioning
confidence: 99%
“…Given that there was an abnormal increase in IL-6 levels, the pulmonary edema could have been attributed to the inflammatory mechanism, by which the overproduction of IL-6 caused from elevated catecholamine levels disrupts the endothelial junction, leading to capillary leakage [6]. Another pathophysiological The FloTrac™-derived value of APCO, which is calculated based on analysis of the peripheral arterial pressure waveform without external calibration, has theoretically a more rapid response than PACO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adzick reporta en una serie de pacientes operadas en Vanderbilt una ocurrencia de edema pulmonar en el postoperatorio inmediato de aproximadamente 8% 44 . Esta alta incidencia se relaciona con uso de tocolíticos durante el intraoperatorio 45 , tratamiento que necesariamente se extiende a las siguientes 48 h del postoperatorio. Reportes de congestión pulmonar han sido descritos especialmente con nitroglicerina 46,47 y agonistas Beta miméticos 48 , aunque en nuestra experiencia el único caso de congestión pulmonar fue en una paciente que recibió nitroglicerina como tocolisis durante el intraoperatorio y se mantuvo con Atósiban posteriormente.…”
Section: Reposición De Fluidosunclassified